Expression of dominant-negative Dmp53 in the adult fly brain inhibits insulin signaling. - Bauer, J.H.; Chang, C.; Morris, S.N.S.; Hozier, S.; Andersen, S.; Waitzman, J.S.; Helfand, S.L. (Proceedings of the National Academy of Sciences of the United States of America, 2007)
In Drosophila melanogaster, p53 (Dmp53) is an important mediator of longevity. Expression of dominant-negative (DN) forms of Dmp53 in adult neurons, but not in muscle or fat body cells, extends lifespan. The lifespan of calorie-restricted flies is not further extended by simultaneously expressing DN-Dmp53 in the nervous system, indicating that a decrease in Dmp53 activity may be a part of the CR lifespan-extending pathway in flies. In this report, we show that selective expression of DN-Dmp53 in only the 14 insulin-producing cells (IPCs) in the brain extends lifespan to the same extent as expression in all neurons and this lifespan extension is not additive with CR. DN-Dmp53-dependent lifespan extension is accompanied by reduction of Drosophila insulin-like peptide 2 (dILP2) mRNA levels and reduced insulin signaling (IIS) in the fat body, which suggests that Dmp53 may affect lifespan by modulating insulin signaling in the fly.